ACTR-31. PHASE 1 STUDY OF AG-881, AN INHIBITOR OF MUTANT IDH1 AND IDH2: RESULTS FROM THE RECURRENT/PROGRESSIVE GLIOMA POPULATION. (5th November 2018) - Mellinghoff, Ingo; Penas-Prado, Marta; Peters, Katherine; Cloughesy, Timothy; Burris, Howard; Maher, Elizabeth; Janku, Filip; Cote, Gregory; De La Fuente, Macarena; Clarke, Jennifer; Steelman, Lori; Le, Kha; et al.
Abstract: INTRODUCTION: Isocitrate dehydrogenase 1 and 2 mutations (mIDH1/2) occur in >70% of low-grade gliomas and secondary glioblastomas, and lead to genetic and epigenetic dysregulation, promoting tumorigenesis. AG-881 is an oral, potent, brain-penetrant inhibitor of mIDH1/2 under phase 1 clinical evaluation in gliomas and other solid tumors. Here we present clinical data from the glioma population. METHODS: Patients with recurrent/progressive mIDH1/2 glioma received AG-881 daily in continuous 28-day cycles. A Bayesian model was used for dose escalation. Dose-limiting toxicity (DLT) definition: Grade 3 AG-881-related adverse event (AE) in Cycle 1 or by sponsor designation. Blood samples were collected for pharmacokinetic (PK)/pharmacodynamic (PD) evaluations. MRI response every 8 weeks by RANO and RANO-LGG criteria. RESULTS: As of 28Mar2018, 52 patients with glioma had received AG-881 and 17 (32.7%) remained on treatment. Grade 2/3 = 90.4%; median age = 42.5 years; IDH1/2: 48/3; median no. prior therapies = 2 (range 1–6). Five initial dose levels tested: 25mg (n=6), 50mg (n=5), 100mg (n=10), 200mg (n=14), and 300mg (n=5). To confirm safety and PK, a 10mg dose level was tested (n=6) and 6 additional patients enrolled in the 50mg cohort. Common (>20%) AEs across glioma patients regardless of attribution: ALT increased (44.2%), AST increased (38.5%), headache (34.6%), fatigue (30.8%), nausea (26.9%), seizure (21.2%). Five patients experienced DLTs at 100mg: Grade 2 ALT/AST that resolved to Grade 1 with dose modification (n=4) or discontinuation (n=1). Among the evaluable glioma population: 2% minor response, 75% stable disease, 21% progressive disease, and 2% missing as best overall response. CONCLUSION: Maximum tolerated dose/recommended phase 2 dose was not reached by Bayesian model; clinical team recommendation was to proceed with doses <100mg in patients with glioma. The 10mg and 50mg doses are being explored in an ongoing perioperative glioma study. Updated safety, PK, and imaging response analyses will be presented.